Interjections in Original and Dubbed Sitcoms in Catalan: A Comparison - Matamala, Anna (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThis article analyses interjections, a very specific element of orality, in a corpus of sitcoms both dubbed into Catalan and originally shot in Catalan. After defining interjections and describing the corpus used to carry out the analysis, a comparison between the number of interjections contained in the dubbed sitcoms of the corpus and the number of interjections included in those originally shot in Catalan is presented. This data is also compared to the percentage of interjections found in a corpus of real spontaneous conversations in Catalan. Finally, the possible effects of the constraints of dubbing on the orality of dubbed products are discussed and the changes interjections undergo during this dynamic process are highlighted.